6Li Structure Information from 2 H (α,α) 2 H Scattering - Massen-Hane, K.; Fraser, P.; Kadyrov, Alisher; Bray, Igor; Amos, K.; Canton, L.; Drumm, D. (2016)
© Copyright owned by the author(s). In this study, we investigate low-energy elastic scattering of 4 He+ 2 H using an effective two-body clusterisation model. We solve the Lippmann-Schwinger equations assuming that coupling effects between channels involving the 2 H bound 3 S 1 state and those of the virtual 1 S 0 state are negligible. Two calculations have been performed; one using a potential that best recreates the 6 Li spectrum, and the other to best recreate the low-energy elastic cross section, for which there is a large amount of experimental data. The potential so prescribed in each case is used for both the 3 S 1 and 1 S 0 channel sets. These calculations show that an effective two-body model suffices to explain many features of the data.